2021
DOI: 10.1111/josi.12425
|View full text |Cite
|
Sign up to set email alerts
|

Police procedural justice and adolescents’ internalization of the law: Integrating self‐determination theory into legal socialization research

Abstract: The procedural justice model is a common framework for understanding how and why fair procedures conveyed by legal authorities (such as police officers) shape the legal socialization process. The present contribution draws upon self-determination theory (SDT) to advance the procedural justice model through its focus on internalization, in terms of identification and external regulation. Study 1 is a questionnaire-based study conducted among 268 Belgian adolescents that provides initial evidence for the increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 97 publications
0
25
0
5
Order By: Relevance
“…A considerable amount of research has found a relationship between youths' attitudes and beliefs regarding the legal system, law, and rules and norms underlying it and delinquent behavior (Cohn et al, 2010(Cohn et al, , 2012Fagan & Piquero, 2007;Fagan & Tyler, 2005;Piquero et al, 2005;Tyler, 2006;Tyler & Fagan, 2008;Tyler & Huo, 2002;Van Petegem et al, 2021). Research has also found that attitudes and beliefs about the system are formed, at least in part, through interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of research has found a relationship between youths' attitudes and beliefs regarding the legal system, law, and rules and norms underlying it and delinquent behavior (Cohn et al, 2010(Cohn et al, , 2012Fagan & Piquero, 2007;Fagan & Tyler, 2005;Piquero et al, 2005;Tyler, 2006;Tyler & Fagan, 2008;Tyler & Huo, 2002;Van Petegem et al, 2021). Research has also found that attitudes and beliefs about the system are formed, at least in part, through interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, understanding legal socialization as part of development is also important because it is the process through which individuals acquire beliefs about societal rules, norms, and the systems that enforce them (Cohn et al, 2012;Cohn & White, 1990;Fagan & Tyler, 2005;Levine & Tapp, 1977;Tyler & Trinkner, 2018). These beliefs become internalized, thereby shaping compliance with rules and the institutions enforcing them (Fagan & Tyler, 2005;Van Petegem et al, 2021).…”
Section: Legal Socialization Of Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Many focus not just upon attitudes and values, but upon what people do (for example, rule violating behavior; e.g., Cole et al, 2021). Finally, there is the use of experimental designs based on vignettes (e.g., Van Petegem et al, 2021).…”
Section: Looking Toward the Futurementioning
confidence: 99%
“…Finally, Van Petegem et al (2021) introduce a new theoretical framework into socialization studies: self-determination theory. Self-determination theory argues that the desire for autonomy is a basic need that motivates internalization and self-regulation.…”
Section: Processes Of Socializationmentioning
confidence: 99%